Pengaruh Promosi, Kualitas Pelayanan, Dan Fasilitas Terhadap Minat Berkunjung Wisatawan Di Pantai Ngliyep Kabupaten Malang - Ferlian Ramadhan; Budi Wahono; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of promotion, service quality, and facilities on the interest of tourists visiting Ngliyep Beach, Malang Regency. This research uses the method of distributing questionnaires or questions, quantitative types. The results of the respondent's recap in the research were 91 respondents and the data correction using the SPSS computer program. The validity and reliability have been fulfilled in the research. Classical assumption test, multiple linear regression, hypothesis testing, and analysis of the coefficient of determination are included in the study as a data analysis tool. Variable Interest in visiting is the dependent variable, the independent variable is Promotion, Service Quality, and Facilities. The results of the study stated that Promotion, Service Quality, and Facilities had a simultaneous and partial effect on Tourist Visiting Interest. Keywords: Promotion, Service Quality, Facilities, Tourist Visiting Interest